Dana, replacement name for the New Zealand talitrid amphipod genus Tara Duncan, 1994 (Crustacea, Amphipoda, Talitridae), preoccupied by Tara Peckham & Peckham, 1886 (Araneae, Salticidae, Amycinae, Astiini) - Lowry, J. K. (Zootaxa, 2011)
Tara Duncan, 1994, was established as a terrestrial genus of New Zealand talitrid amphipods, with the type species Orchestia sylvicola Dana, 1852. It was recently discovered to be a junior homonym of Tara Peckham & Peckham, 1886, a genus of salticid spiders (Araneae, Salticidae, Amycinae, Astiini). Tara Peckham & Peckham, 1886, is a valid name in current use for a small endemic genus of Australian jumping spiders recently revised by Zabka (1987). Tara Duncan, 1994, appears in the literature at least three times: in the original description of the genus (Duncan 1994), in identification keys to the terrestrial amphipods of New Zealand (Fenwick & Webber 2008), and in the recent inventory of New Zealand biodiversity (Webber et al. 2010). The new name, Dana, is proposed to replace Tara Duncan, 1994.